The Effect of KSK-94, a Dual Histamine H3 and Sigma-2 Receptor Ligand, on Adipose Tissue in a Rat Model of Developing Obesity - Magdalena Kotańska; Monika Zadrożna; Monika Kubacka; Kamil Mika; Katarzyna Szczepańska; Barbara Nowak; Alessio Alesci; Anthea Miller; Eugenia Rita Lauriano; Katarzyna Kieć-Kononowicz (MDPI AG, 2024)
Background: Numerous studies highlight the critical role that neural histamine plays in feeding behavior, which is controlled by central histamine H3 and H1 receptors. This is the fundamental motivation for the increased interest in creating histamine H3 receptor antagonists as anti-obesity medications. On the other hand, multiple other neurotransmitter systems have been identified as pharmacotherapeutic targets for obesity, including sigma-2 receptor systems. Interestingly, in our previous studies in the rat excessive eating model, we demonstrated a significant reduction in the development of obesity using dual histamine H3/sigma-2 receptor ligands. Moreover, we showed that compound KSK-94 (structural analog of Abbott's A-331440) reduced the number of calories consumed, and thus acted as an anorectic compound. Therefore, in this study, we extended the previous research and studied the influence of KSK-94 on adipose tissue collected from animals from our previous experiment. Methods: Visceral adipose tissue was collected from four groups of rats (standard diet + vehicle, palatable diet + vehicle, palatable diet + KSK-94, and palatable diet + bupropion/naltrexone) and subjected to biochemical, histopathological, and immunohistochemical studies. Results: The obtained results clearly indicate that compound KSK-94 prevented the hypertrophy and inflammation of visceral adipose tissue, normalized the levels of leptin, resistin and saved the total reduction capacity of adipose tissue, being more effective than bupropion/naltrexon in these aspects. Moreover, KSK-94 may induce browning of visceral white adipose tissue. Conclusion: Our study suggests that dual compounds with a receptor profile like KSK-94, i.e., targeting histamine H3 receptor and, to a lesser extent, sigma-2 receptor, could be attractive therapeutic options for patients at risk of developing obesity or with obesity and some metabolic disorders. However, more studies are required to determine its safety profile and the exact mechanism of action of KSK-94.